Meeting the guidelines: Implementing a distress screening intervention for veterans with cancer. Issue 12 (10th October 2020) - Azizoddin, Desiree R.; Lakin, Joshua R.; Hauser, Joshua; Rynar, Lauren Z.; Weldon, Christine; Molokie, Robert; Enzinger, Andrea C.; Payvar, Susan; Martin, Joanna L.
Abstract: Background: Guidelines recommend systematic evaluation of distress screening and referral for cancer patients. Implementation remains a notable gap for cancer centers serving disadvantaged communities. We present the implementation of a distress screening program within a Veterans Affairs hospital oncology clinic, serving a majority African American (AA) male population of low socioeconomic status (SES). Methods: The Coleman Foundation funded this program supporting a palliative care physician and psychologist to implement screening in a phased approach as follows: (1) Organizing key stakeholders, (2) educating clinical staff, (3) delivering distress screening, (4) generating documentation, and (5) implementing clinical action and referral pathways. We utilized validated measures in the "Patient Screening Questions for Supportive Care" screening tool. Results: This program was unsuccessful in screening all veterans with cancer; however, we were able to implement 3 years of longitudinal screening. In distress screens from the initial program period ( n = 253), patients were primarily males (95.6%) of older age ( m = 70, standard deviation = 9.45), AA (76.4%), with various cancers of advanced disease (69%). Males reported moderate psychosocial distress and elevated financial needs. For males with elevated psychosocial distress ( n = 63, PHQ‐4 ≥3), 36% were previously connected with psychosocial services. Following screening, engagement increased as the majority (77%) established psychosocial care. Conclusions: This screening program had mixed success. Centralized program staff and available supportive care referrals were critical for program implementation. Screening may have increased engagement in social work/mental health services for males of low SES. Screening programs should be tailored to the needs of underserved communities with accessible housing/food subsidies.